Gender, Discourse and Ideology in Italian - Formato, Federica (Palgrave Studies in Language, Gender and Sexuality, 2019)
This book analyses gendered language in Italian, shedding light on how the Italian language constructs and reproduces the social imbalance between women and men, and presenting indirect and direct instances of asymmetrical constructions of gender in public and private roles. The author examines linguistic treatments of women in politics and the media, as well as the gendered crime of femminicidio, i.e. the killing of women by their (former) partners. Through the combination of corpus linguistics, surveys, and discourse analysis, she establishes a new approach to the study of gendered Italian, a framework which can be applied to other languages and epistemological sites. This book will be of particular interest to students and scholars of sociolinguistics, language and gender, discourse analysis, Italian and other Romance languages. Federica Formato is an independent scholar who has taught linguistics at various UK universities. She has published on the topics of direct and indirect instances of sexism in Italian from quantitative and qualitative perspectives, and gender and language in the law. Her research interests include gender, politics, violence against women and corpus linguistics.